2007
DOI: 10.1007/s00253-007-1194-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of wine fermentation temperature on the synthesis of yeast-derived volatile aroma compounds

Abstract: The yeast Saccharomyces cerevisiae synthesises a variety of volatile aroma compounds during wine fermentation. In this study, the influence of fermentation temperature on (1) the production of yeast-derived aroma compounds and (2) the expression of genes involved in aroma compounds' metabolism (ADH1, PDC1, BAT1, BAT2, LEU2, ILV2, ATF1, ATF2, EHT1 and IAH1) was assessed, during the fermentation of a defined must at 15 and 28 degrees C. Higher concentrations of compounds related to fresh and fruity aromas were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
178
2
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(210 citation statements)
references
References 32 publications
16
178
2
6
Order By: Relevance
“…The expression of the actin gene, reported to be constitutively expressed under bioreactor wine fermentation conditions (Riou et al 1997), was used as reference, as in previous studies (Molina et al 2007). All data obtained with the other genes were normalized relative to this gene.…”
Section: Methodsmentioning
confidence: 99%
“…The expression of the actin gene, reported to be constitutively expressed under bioreactor wine fermentation conditions (Riou et al 1997), was used as reference, as in previous studies (Molina et al 2007). All data obtained with the other genes were normalized relative to this gene.…”
Section: Methodsmentioning
confidence: 99%
“…bayanus strain EC1118 (Lallemand Inc., Blagnac, France). This commercial wine yeast, used worldwide for both red and white winemaking, is considered a fast and robust fermenting strain, with a neutral contribution to the wine aroma (Molina et al, 2007). The chemically defined medium MS300, similar in composition to typical grape juice (Bely et al, 1990), was used with a little modification.…”
Section: Strain and Culture Mediummentioning
confidence: 99%
“…The yeast influence on wine aroma is not only species-dependent but relevant variations are also showed at strain level [6,7]. In this regard, each wine yeast strain produces different aroma compounds, higher alcohols, acetate esters, ethyl esters and aldehydes that characterize the final wine bouquet [4]. Indeed, different strains of S. cerevisiae can metabolize flavor active compounds that characterized different grape varieties to produce volatile compounds [8].…”
Section: Introductionmentioning
confidence: 99%
“…Molina et al [4] evaluated the influence of fermentation temperature on the production of yeast-derived aroma compounds together with the expression of genes involved, during the fermentation of a defined must at 15 and 28 • C. They found that the production of volatile aroma compounds varied according to yeast growth stage. In particular, higher concentrations of compounds related to fresh and fruity aromas were found at low temperature, while higher concentrations of flowery related aroma compounds were found at 28 • C. In addition, Torijia et al [5] demonstrated that low temperatures restricted yeast growth and lengthened the fermentations.…”
Section: Introductionmentioning
confidence: 99%